Time-Compression: Systems Concerns, Usage, and Benefits - Grudin, Jonathan; Gupta, Anoop; He, Liwei; Omoigui, Nosa; Sanocki, Elizabeth; He, Li-wei (1999)
With the proliferation of online multimedia content and the popularity of multimedia streaming systems, it is increasingly useful to be able to quickly skim and browse multimedia. A key technique that enables quick browsing of multimedia is time-compression . Prior research has described how speech can be time-compressed (shortened in duration) while preserving the pitch of the audio. However, client-server systems providing this functionality have not been available. In this paper, we first describe the key tradeoffs faced by designers of streaming multimedia systems deploying time-compression. The implementation tradeoffs primarily impact the granularity of time-compression supported (discrete vs. continuous) and the latency (wait-time) experienced by users after adjusting degree of time-compression. We report results of user studies showing impact of these factors on the average-compression-rate achieved. We also present data on the usage patterns and benefits of time compression. Overall, we show significant time-savings for users and that considerable flexibility is available to the designers of client-server streaming systems with time compression.